Pharmacoeconomics of PCSK9 inhibitors in 103 hypercholesterolemic patients referred for diagnosis and treatment to a cholesterol treatment center - Shah, Parth (Lipids Health Dis, 2016)
BACKGROUND: PCSK9 inhibitor therapy has been approved by the FDA as an adjunct to diet-maximal tolerated cholesterol lowering drug therapy for adults with heterozygous familial hypercholesterolemia (HeFH) or clinical atherosclerotic cardiovascular disease (ASCVD) with suboptimal LDL cholesterol (LDLC) lowering despite maximal diet-drug therapy. With an estimated ~24million of US hypercholesterolemic patients potentially eligible for PCSK9 inhibitors, costing ~ $14,300/patient/year, it is important to assess health-care savings arising from PCSK9 inhibitors vs ASCVD cost. METHODS: In 103 patients with HeFH, and/or ASCVD and/or suboptimal LDLC lowering despite maximally tolerated diet-drug therapy, we assessed pharmacoeconomics of PCSK9 inhibitor therapy with lowering of LDLC. For HeFH diagnosis, we applied Simon Broome’s or WHO Dutch Lipid Criteria (score >8). Estimates of direct and indirect costs for ASCVD events were calculated using American Heart Association (AHA), U.S. DHHS, Healthcare Bluebook, and BMC Health Services Research databases. We used the ACC/AHA 10-year ASCVD risk calculator to estimate 10-year ASCVD risk and estimated corresponding direct and indirect costs. Assuming a 50 % reduction in ASCVD events on PCSK9 inhibitors, we calculated direct and indirect health-care savings. RESULTS: We started 103 patients (58 [56 %] women and 45 [44 %] men), on either alirocumab (62 %) or evolocumab (38 %), median age 63, BMI 29.0, and LDLC 149 mg/dl. Of the 103 patients, 28 had both HeFH and ASCVD, 33 with only ASCVD, 33 with only HeFH, and 9 had neither. Of the 103 patients, 61 had a first ASCVD event at median age 55 and on best tolerated cholesterol-lowering therapy median LDLC was 137 mg/dl. In these 61 patients, total direct costs attributable to ASCVD were $8,904,361 ($4,328,623 direct, $4,575,738 indirect), the median 10-year risk of a new CVD event was calculated to be 13.1 % with total cost $1,654,758. Assuming a 50 % reduction in ASCVD events on PCSK9 inhibitors in our 61 patients, $4,452,180 would have been saved in the past; and future 10-year savings would be $1,123,345. CONCLUSION: In the 61 CVD patients, net costs/patient/year were estimated to be $7,000 in the past, with future 10-year intervention net costs/patient/year being $12,459, both below the $50,000/year quality adjusted life-year gained by PCSK9 inhibitor therapy.